Application of HAZOP, LOPA and SIL to the alkylation unit catalyzed with hydrofluoric acid at Ecopetrol Refinery in Cartagena – Colombia - Figueroa Jiménez, Stefanny Paola (Ingenierias, 2016)
Tesis (Ingeniero Químico).-- Universidad de San Buenaventura, Facultad de Ingeniería Arquitectura Artes y Diseño, Programa de Ingeniería Química, 2015